2017
DOI: 10.1089/neu.2016.4498
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Antibody Response after Cervical Spinal Cord Injury

Abstract: The immune system plays a critical and complex role in the pathobiology of spinal cord injury (SCI), exerting both beneficial and detrimental effects. Increasing evidence suggests that there are injury level-dependent differences in the immune response to SCI. Patients with traumatic SCI have elevated levels of circulating autoantibodies against components of the central nervous system, but the role of these antibodies in SCI outcomes remains unknown. In rodent models of mid-thoracic SCI, antibody-mediated aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 69 publications
2
37
1
Order By: Relevance
“…Serum IgG levels in SCI patients are significantly higher at 1 month after injury compared to healthy subjects, while IgM levels fail to reach statistical significance (Figures 1A,B ). In experimental models, at the acute phase, total IgG and IgM serum levels increase after low thoracic lesions ( 3 ) and decrease after cervical lesions ( 16 ). Contrasting with these observations, in our study neither neurological level of injury nor severity affects total IgG or IgM serum levels (Figures 1C – F ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum IgG levels in SCI patients are significantly higher at 1 month after injury compared to healthy subjects, while IgM levels fail to reach statistical significance (Figures 1A,B ). In experimental models, at the acute phase, total IgG and IgM serum levels increase after low thoracic lesions ( 3 ) and decrease after cervical lesions ( 16 ). Contrasting with these observations, in our study neither neurological level of injury nor severity affects total IgG or IgM serum levels (Figures 1C – F ).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, it has been reported that high thoracic lesions, but not low thoracic, inhibit the production of antibodies after immunization with exogenous antigens in mice ( 8 , 15 ). However, cervical injuries increase AAb levels against spinal cord self-antigens ( 16 ). These opposed results between the responses of antibodies against exogenous and self-antigens may be explained by the observations in rodent experimental models showing that (i) SCI only impairs the generation of new antibody responses but preserves already existing immunity ( 17 ) and that (ii) AAbs detected after SCI may exist before lesion ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that cervical SCI results in disturbed peripheral adaptive immune responses in the spleen of rats [ 15 ] and blood of humans [ 16 ]. Others have shown dysregulation of peripheral adaptive immunity in the spleen [ 10 ], blood [ 17 ] and lymph nodes (LNs) [ 9 ] in experimental and clinical thoracic SCIs.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, the spleen plays an important role in erythrocyte turnover, adaptive immunity, antibody production, and, more recently revealed, the mobilization of monocytes/macrophages (Mφ) following tissue injury [ 4 ]. In the context of high-level SCI, several studies have evaluated dysfunctional antibody synthesis following loss of splenic sympathetic preganglionic innervation [ 5 7 ] and the production of autoantibodies against spinal cord tissue [ 8 ]. Yet, equally important is the acute response to trauma-induced inflammation, where the spleen initiates production of tumor necrotic factor-α (TNFα), mostly by resident Mφs, and in turn influences the recruitment of immune cells to the inflamed tissue [ 9 ].…”
Section: Introductionmentioning
confidence: 99%